2014
DOI: 10.1002/art.38741
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Adalimumab as the First and Second Biologic Agent in Juvenile Idiopathic Arthritis: The German Biologics JIA Registry

Abstract: Objective. To evaluate the efficacy and safety of adalimumab in patients with juvenile idiopathic arthritis (JIA).Methods. Baseline demographic and clinical characteristics and disease activity parameters were prospectively documented in the German Biologics JIA Registry. Efficacy was determined using the American College of Rheumatology (ACR) Pediatric (Pedi) response criteria and the Juvenile Arthritis Disease Activity Score based on a 10-joint count (JADAS-10). Safety assessments were based on adverse event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 36 publications
7
46
3
3
Order By: Relevance
“…However, ADA showed a better safety profile than IFX (p = 0.008). Interestingly, we found a much lower rate of AE for ADA than in the German Biologics JIA registry (10.6 vs 50.9 per 100 PY, respectively) 14 . In this registry, however, all JIA subtypes with various comorbidities are included and this may explain the difference.…”
Section: Rheumatologycontrasting
confidence: 52%
“…However, ADA showed a better safety profile than IFX (p = 0.008). Interestingly, we found a much lower rate of AE for ADA than in the German Biologics JIA registry (10.6 vs 50.9 per 100 PY, respectively) 14 . In this registry, however, all JIA subtypes with various comorbidities are included and this may explain the difference.…”
Section: Rheumatologycontrasting
confidence: 52%
“…There is, however, ample data from original studies and long term outcome studies to enable a historical comparison to the efficacy of high doses of biologics to standard doses or those on traditional DMARDs alone. None of the adverse events we report are inconsistent with the findings noted in prior published experience with these agents, and the nearly 70% response rate is convergent with prior reports as well [17][18][19][20][21]. Notably, Lovell et al demonstrated rates of SAEs to be 0.13 per patient-year, and rates of serious infections were 0.04 per patient-year, in a total etanercept exposure of 225 patientyears.…”
Section: Discussionsupporting
confidence: 75%
“…In regard to the safety of biologics, there have been increasing data on long-term outcomes, with reassuring findings reported in several studies [5,[10][11][12][13]. However, the safety and efficacy of higher dose biologics for pediatric patients with a diversity of diseases have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Written informed consent was obtained from all parents and eligible patients, and data were collected in pseudonymized form as approved by the ethics committee. Since the year 2000, patients newly starting on-label treatment with ETA, and since 2008 with ADA, were included in the registry (16)(17)(18). Patients without exposure to a biologic agent but starting with MTX were recruited as a control cohort from 2005 to 2011, until the target of 1,500 patients was reached.…”
Section: Methodsmentioning
confidence: 99%